Treatment of Early Breast Cancer The 18th St. Gallen International Breast Cancer Consensus Conference against the Background of Current German Treatment Recommendations Behandlung des frühen Mammakarzinoms 18. Internationaler St.-Gallen-Konsens vor dem Hintergrund der aktuellen deutschen Therapieempfehlungen diskutiert - Untch, Michael; Banys-Paluchowski, Maggie; Brucker, Sara Y.; Budach, Wilfried; Denkert, Carsten; Ditsch, Nina; Fasching, Peter; Haidinger, Renate; Heil, Jörg; Jackisch, Christian; Janni, Wolfgang; Kolberg, Hans Christian; et al. (Geburtshilfe und Frauenheilkunde, 2023)
This year's 18th St. Gallen (SG) consensus conference on the treatment of early breast cancer (SGBCC: St. Gallen International Breast Cancer Conference) focused on practice-oriented questions. The individual situation and risk-benefit assessment were discussed in great detail. As in previous years, a German working group of leading breast cancer experts presented the results of the international SGBCC 2023 against the background of German treatment recommendations – especially the updated treatment recommendations of the Arbeitsgemeinschaft Gynäkologische Onkologie e.V. (AGO) – for everyday clinical practice in Germany. The German treatment recommendations of AGO are based on the current evidence. The comparison with the clinical approach in Germany has proven useful, as the SGBCC panel consists of experts from different countries and disciplines. That is why country-specific characteristics can be incorporated into the SGBCC recommendations.
CRIS-Team Scopus Importer:2024-12-16
Keywords: (neo)adjuvant systemic therapy; early-onset breast cancer; genetics; pathology; radiotherapy; St. Gallen Consensus 2023; surgery